Gluten-related disorders: certainties, questions and doubts. (3rd October 2017) - Valenti, Simona; Corica, Domenico; Ricciardi, Luisa; Romano, Claudio
Abstract: In the last decade, the ingestion of gluten, a heterogeneous complex of proteins present in wheat, rice, barley and probably in oats, has been associated with clinical disorders, such as celiac disease, wheat allergy and recently to non-celiac gluten sensitivity or wheat intolerance syndrome. Gluten-related disorders, which are becoming epidemiologically relevant with an estimated global prevalence of about 5%, require the exclusion of gluten from the diet. For the past 5 years, an important shift in the availability of gluten-free products, together with increased consumption in the general population, has been recorded and is estimated to be about 12–25%. Many people follow a self-prescribed gluten-free diet, despite the fact that the majority have not first been previously excluded, or confirmed, as having gluten disorders. They rely on claims that a gluten-free diet improves general health. In this review, we provide an overview of the clinical disorders related to gluten or wheat ingestion, pointing out the current certainties, open questions, possible answers and several doubts in the management of these conditions. KEY MESSAGE: Incidence of gluten-related disorders is increased in the last decade and self-diagnosis is frequent with inappropriate starting of a gluten-free diet. Gluten and wheat are considered as the most important triggers to coeliac disease, wheat allergy and non-celiac gluten sensitivity. Pediatricians, allergologist and gastroenterologist are involved in the management of these conditions and appropriate diagnostic protocols are required.